Microbleeds in ischemic vs hemorrhagic strokes on novel oral anticoagulants. (16th April 2018) - Purrucker, J. C.; Wolf, M.; Haas, K.; Siedler, T.; Rizos, T.; Khan, S.; Heuschmann, P. U.; Veltkamp, R.
Abstract : Objectives: To identify differences in clinical characteristics and severity of cerebral small vessel disease (CSVD) including cerebral microbleeds (CMBs), between patients suffering ischemic stroke (IS) or intracerebral hemorrhage (ICH) while taking novel (non‐vitamin K antagonists) oral anticoagulants (NOACs). Methods: Multicenter, prospective, observational cohort study performed at 38 centers between 2012 and 2015. We compared demographics, comorbidity, and functional status (before and after stroke) between NOAC‐IS and NOAC‐ICH patients. Extent of white matter lesions (WML), and location and counts of CMBs were analyzed in a subgroup of patients for whom MRI including hemorrhage‐sensitive sequences was available. Results: A total of 351 patients were included (290 NOAC‐IS, 61 NOAC‐ICH). Functional status was worse in NOAC‐ICH patients before and after stroke. No significant differences were found for demographic variables and cardiovascular comorbidity. In the subgroup with available MRI (n = 116), the proportion of patients with at least one CMB was higher in NOAC‐ICH than in NOAC‐IS (15/19 [79%] vs 36/97 [37%], P  < .001), as was the absolute number of CMBs (median 5 [IQR 1‐24] vs 0 [0‐1], P  < .001). WML were more extensive in NOAC‐ICH than in NOAC‐IS patients. Adjusted for WML, logistic regression analysis showed higher odds of NOAC‐ICH in patients with CMB than without (OR 5.60 [1.64‐19.14], P  = .006). Conclusions: Patients with NOAC‐ICH have similar clinical characteristics but a higher prevalent burden of CSVD compared to NOAC‐IS. The role of neuroimaging in selection of patients for anticoagulation with NOAC requires further investigation in longitudinal studies.